Analisis Framing Pemberitaan Bullying Bystanders Kasus Mario Dandy di Detik.com - Suardi; Viandira, Adisty (Jurnal Indragiri Penelitian Multidisiplin, 2025)
This study analyzes the framing of news coverage regarding the role of bystanders in the bullying case involving Mario Dandy on the Detik.com news site. The study aims to understand how this news coverage is positioned in the media and how media framing can influence public perception of the event. The method used is framing analysis with Robert Entman's approach, which consists of four main elements: problem definition, interpretation of consequences, moral evaluation, and recommended actions. The results show that the coverage on Detik.com tends to focus on the psychological impact on the victim and criticizes the passive behavior of the bystanders who did not intervene in the bullying incident. This study provides insights into how media can influence public views on social phenomena, particularly in relation to bullying and the role of bystanders.